Trženje in druge poslovne funkcije - prijatelji ali sovražniki? - Rojšek, Iča (Akademija MM, 1998)
Coordination between marketing and other business functions is not simple at all. The problems related to this are the result of the core differences in views on what the principal objective of a company is or what its role in the economy is, and also on the priority order of certain factors which contributeto the business sucess of the company. Therefore, conflicts are bound to appear. In this paper the relationships and the most frequent conflicts between marketing and other functions (production, purchasing, R&D, finance, and sales) are described. The paper concludes with the results of the exploratory research on a sample of 46 Slovene industrial companies.
Keywords: business success; companies; industrial companies; industrijska podjetja; marketing; podjetja; poslovni uspeh; Slovenia; Slovenija; trženje